2020
DOI: 10.14218/jcth.2020.00043
|View full text |Cite
|
Sign up to set email alerts
|

Liver Dysfunction and Its Association with the Risk of Death in COVID-19 Patients: A Prospective Cohort Study

Abstract: Background and Aims: Coronavirus disease 2019 (COVID-19) is a new respiratory infectious disease caused by severe acute respiratory syndrome coronavirus-2 (commonly known as SARS-CoV-2) with multiple organ injuries. The aim of this study was to analyze COVID-19-associated liver dysfunction (LD), its association with the risk of death and prognosis after discharge. Methods: Three-hundred and fifty-five COVID-19 patients were recruited. Clinical data were collected from electronic medical records. LD was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…COVID-19 infection causes systemic responses in the body, including the liver ( 22 , 23 ), kidney ( 22 , 24 , 25 ), heart ( 24 , 26 ), and even the brain ( 27 , 28 ). Consistent with previous reports ( 29 , 30 ), we found that patients with severe COVID-19 infection have significantly increased ALT, AST, ALP, TBIL, and DBIL levels, especially AST levels, which are much higher than the normal range. The level of BUN is also significantly increased in patients with severe COVID-19 infection.…”
Section: Discussionsupporting
confidence: 93%
“…COVID-19 infection causes systemic responses in the body, including the liver ( 22 , 23 ), kidney ( 22 , 24 , 25 ), heart ( 24 , 26 ), and even the brain ( 27 , 28 ). Consistent with previous reports ( 29 , 30 ), we found that patients with severe COVID-19 infection have significantly increased ALT, AST, ALP, TBIL, and DBIL levels, especially AST levels, which are much higher than the normal range. The level of BUN is also significantly increased in patients with severe COVID-19 infection.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, SARS-CoV-2-evoked renal dysfunction was not fully recovered in 2 weeks after discharge. Mounting evidences have confirmed that SARS-CoV-2 injection evoked multiple organ injuries, primarily containing liver dysfunction, myocardial injury, lymphocyte reduction and even respiratory failure [8][9][10][11]. In this research, the levels of serum uric acid, urea nitrogen, creatinine, cystatin C and eGFR were detected and renal dysfunction was evaluated among COVID-19 patients between on admission and discharge.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies have demonstrated that COVID-19 patients mainly accompanied with fever, diarrhea, dry cough, lymphocyte reduction and radiographic evidence of pneumonia [7]. Now, more and more studies have confirmed that SARS-CoV-2 not only evoked severe acute respiratory syndrome, but also induced multiple organ injuries, such as myocardial injury, lymphocyte reduction and even liver dysfunction [8][9][10][11]. Nevertheless, the clinical characteristics of renal dysfunction caused by SARS-CoV-2 are rarely described.…”
Section: Introductionmentioning
confidence: 99%
“…Acute kidney injury (AKI) has been observed in 3%–15% of COVID-19 patients ( 6 ) and ≤25% in critically-ill COVID-19 patients ( 7 ). Greater possibility can be presented for AKI among patients with severe acute respiratory distress syndrome (ARDS), which necessitates invasive mechanical ventilation, especially for older patients or those with comorbidities such as hypertension or type 2 diabetes mellitus (T2DM) ( 8 ). Recent studies have suggested that acute renal damage can occur in the early stages of COVID-19, which is associated with death ( 5 , 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%